Synthesis of aromatic poly(amide-imide)s from novel diimide-diacid (DIDA) containing sulphone and bulky pendant groups by direct polycondensation with various diamines - Patil, Prashant S.; Pal, Ravindra R.; Salunkhe, Manikrao M.; Maldar, Noormahamad N.; Wadgaonkar, Prakash P. (European Polymer Journal, 2007)
A novel diimide-diacid (DIDA) monomer, 4-{4-[(4-methyl phenyl) sulphonyl]}-1,3-bis-trimellitoimido benzene containing sulphone and bulky pendant groups was successfully synthesized and used to synthesize a series of wholly aromatic poly(amide-imide)s (PAIs) by direct polycondensation method. The direct polycondensation of newly synthesized DIDA with different diamines was carried Out via Yamazaki's phosphorylation method using triphenyl phosphite and pyridine system. The resulting poly(amide-imide)s were obtained in quantitative yields with inherent viscosities 0.36-0.47 dl/g in DMAc at 30 +/- 0.1 degrees C. The poly(amide-imide)s were amorphous and were readily soluble in various solvents such as N-methyl-2-pyrrolidinone (NMP), NN-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), and pyridine. Tough and flexible films were obtained by casting their DMAc solution. According to thermogravimetric analysis, the polymers were fairly stable up to temperature around 396 degrees C, and 10% weight losses in the temperature range of 476-511 degrees C that showed good thermal stabilities of these polymers. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: direct polycondensation; poly(amide-imide)s; sulphone and bulky pendant groups; thermally stable polymers

Synthesis and properties of new polybenzoxazines containing (substituted) cyclohexyl moieties - Kumar, K. S. Santhosh; Nair, C. P. Reghunadhan; Ninan, K. N.; Kulkarni, A. D.; Wadgaonkar, P. P. (Polymers for Advanced Technologies, 2009)
A series of new polybenzoxazines were synthesized based on diphenols containing (substituted) cyclohexyl moiety and were characterized by FT-IR, (1)H-NMR, and (13)C-NMR spectroscopy. These new benzoxazine monomers exhibited better processability with lower peak cure temperature and a wide cure controllable window (CCW) as manifested in differential scanning calorimetric analysis. The cure analysis was performed by FT-IR spectroscopy. Glass transition temperature of new polybenzoxazines varied from 170 to 205 degrees C. The cyclohexyl bridge groups facilitated ring opening, resulting in polymer with improved thermal stability in comparison to bisphenol A-based benzoxazine as assessed by the various thermal analyses. The water contact angles of polybenzoxazines containing (substituted) cyclohexyl moieties were higher than that of bisphenol A-based polybenzoxazine, implying their higher hydrophobicity. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: Hydrophobicity; polybenzoxazines; thermally stable polymers